Pathophysiology and Imaging Diagnosis of Demyelinating Disorders - Evanthia Bernitsas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Demyelinating disorders are chronic autoimmune disorders characterized by inflammation, demyelination, axonal degeneration, and neuronal loss. They have complex pathophysiology and diverse clinical presentations. The etiology of these disorders lies in the interaction between genetic and environmental factors. Due to the complexity in pathophysiology and presentation, diagnosis and treatment can be challenging. Advanced technology, including modern imaging techniques, as well as optical coherence tomography (OCT), enrich our understanding of the disease process, improve diagnostic accuracy, and may guide treatment decisions.